2015
DOI: 10.1038/onc.2015.157
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic phosphorylation of Bloom helicase at Thr182 is required for its proteasomal degradation and maintenance of chromosomal stability

Abstract: Mutations in Bloom helicase (BLM) lead to Bloom Syndrome (BS). BS is characterized by multiple clinical manifestations including predisposition to a wide spectrum of cancers. Studies have revealed the mechanism of BLM recruitment after stalled replication and its role during the repair of DNA damage. We now provide evidence that BLM undergoes K48-linked ubiquitylation and subsequent degradation during mitosis due to the E3 ligase, Fbw7α. Fbw7α carries out its function after GSK3β- and CDK2/cyclin A2-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…This mechanism of BLM recruitment to DSBs is in contrast to the processes characterized for its localization to the stalled replication forks 5 , where BLM recruitment predominantly depends RNF8/RNF168-mediated BLM ubiquitylation. Further these BLM ubiquitylation events differ from MIB1 and Fbw7α mediated polyubiquitylation of BLM, both of which lead to BLM degradation by 26S proteasome 32 , 33 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This mechanism of BLM recruitment to DSBs is in contrast to the processes characterized for its localization to the stalled replication forks 5 , where BLM recruitment predominantly depends RNF8/RNF168-mediated BLM ubiquitylation. Further these BLM ubiquitylation events differ from MIB1 and Fbw7α mediated polyubiquitylation of BLM, both of which lead to BLM degradation by 26S proteasome 32 , 33 .…”
Section: Discussionmentioning
confidence: 86%
“…Recently multiple mechanisms involving post-translation modifications of BLM have been deciphered. These include mechanisms which regulate the constitutive expression of BLM 40 , its interaction with TopBP1 and thereby conferring stability 33 , its turnover in both mitosis and G1-phase 32 , 33 and recruitment to PML-NBs 41 . It is quite possible that some these processes that regulate BLM cellular functions may act in close coordination with mechanisms by which BLM responds and ultimately repairs DSBs in different phases of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FBW7 could have multiple substrates involved in various DNA repair processes. For instance, it was recently shown that bloom helicase (BLM) is targeted by FBW7 during mitosis [59]. As FBW7 deficiency exhibits more profound cellular hypersensitivity to MMC compared with cells with the FAAP20 SA mutant, we do not exclude the possibility that FBW7 may have other substrates required for DNA ICL repair.…”
Section: Discussionmentioning
confidence: 92%
“…Immunofluorescence, reverse-transcription PCR, matrigelinvasion assays, transmission electron microscopy Immunofluorescence for SOD2 and AcLys68 SOD2 was carried out as described (Kharat et al, 2015). Imaging was carried out by using a 63×/1.2 oil immersion objective.…”
mentioning
confidence: 99%